PROJECT IMPLEMENTATION DERADICALIZATION IN INDONESIA - Agus Fatuh Widoyo; Prajanata Bagiananda Mulia (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2024)
Indonesia is a country with a majority Muslim population. However, not all of the principles of his teachings are easily accommodated in the existing government system. Even some of his teachings listed in the discussion of fiqh were suspected of containing elements of radicalism that could encourage acts of terrorism. The purpose of this paper is to discuss the discourse on the implementation of deradicalization echoed by the Indonesian government. Using a qualitative descriptive research method, this study found several conclusions: first, deradicalization is a form of government intervention in controlling the religious understanding of Muslims. second, deradicalization is a program that stems from suspicion of several Islamic teachings. third, the government implements deradicalization programs through various programs such as education, religion, social and law.